Scalable reputation management with trustworthy user selection for P2P MMOGs. (29th December 2008) - Huang, Guan-Yu; Hu, Shun-Yun; Jiang, Jehn-Ruey
Recent research on Peer-to-Peer Massively Multiplayer Online Games (P2P MMOGs) has tried to find more scalable and affordable solutions to build virtual environments via the resource sharing of clients. However, P2P approaches face the problem of client misbehaviours where game rules are not processed properly, undermining a game's fairness and normal operations. In this paper, we present REPS, a distributed reputation management system for P2P MMOGs that allows trustworthy clients be identified to perform important tasks. REPS first considers the generation, storage, and query for certain reputation factors that could be the basis to evaluate user trustworthiness. We then propose Trustworthy user Selection (TuS) to adjust the weights of each factor to give preference to the more important ones. Based on the mutual rating among users and reputation queries, REPS provides a scalable and reliable mechanism to facilitate decision making, from choosing trustworthy superpeers, to deciding whether to interact with particular users.